Effects of traits, self-motivation and managerial skills on nursing intrapreneurship - Marques, C.; Marques, C.; Ferreira, J.; Ferreira, F. (International Entrepreneurship and Management Journal, 2019)
Following the introduction of quasi-markets into publicly funded healthcare systems, nurse intrapreneurs who create innovations within these systems have become increasingly important to improving healthcare outputs. This study sought to examine how self-motivation and managerial skills mediate the influence of entrepreneurial traits on nurses’ intrapreneurial intentions in the Portuguese National Health Service. A structural equation model was assessed using primary data collected from a sample of 536 nurses working at seven public hospitals in Portugal. The results suggest that nurses who are more determined to become intrapreneurs are more likely to take risks, more self-confident about their managerial skills and slightly more self-motivated. In addition, while innovativeness has no significant effect, proactivity contributes to increasing nurses’ self-confidence in their own skills.